Babies in therapy, psychoanalytic interventions for infants and their parents - Anzieu-Premmereur, Christine (Frontiers in Psychiatry, 2022)
Babies in Therapy: Psychoanalytic Interventions with infants and Parents Research in infancy, psychoanalytic infant observation and clinical work with parents and babies help to understand the nature of early relationship disorders. Clinical examples show that in psychoanalytic theory, notions of depressive position, early defence mechanisms, transference, psychosomatic reactions to depressive emotions, are important to provide the therapist with new tools for intervention and efficiency. The profound effect of early disappointments with the feeling of being helplessly abandoned has been studied by many psychoanalysts who emphasize that a disturbance in the relationship to the caregiver can causes a psychic economy concentrated on the avoidance of anxiety, leaving less energy for development. Psychoanalytic thinking and understanding of early symptoms can provide new parents and suffering babies early interventions that have a therapeutic value and preventive capability for future narcissistic painful issues.